Genomic architecture of habitat‐related divergence and signature of directional selection in the body shapes of Gnathopogon fishes. Issue 16 (30th July 2015) - Kakioka, Ryo; Kokita, Tomoyuki; Kumada, Hiroki; Watanabe, Katsutoshi; Okuda, Noboru
Abstract Evolution of ecomorphologically relevant traits such as body shapes is important to colonize and persist in a novel environment. Habitat‐related adaptive divergence of these traits is therefore common among animals. We studied the genomic architecture of habitat‐related divergence in the body shape of Gnathopogon fishes, a novel example of lake–stream ecomorphological divergence, and tested for the action of directional selection on body shape differentiation. Compared to stream‐dwelling Gnathopogon elongatus, the sister species Gnathopogon caerulescens, exclusively inhabiting a large ancient lake, had an elongated body, increased proportion of the caudal region and small head, which would be advantageous in the limnetic environment. Using an F2 interspecific cross between the two Gnathopogon species (195 individuals), quantitative trait locus (QTL) analysis with geometric morphometric quantification of body shape and restriction‐site associated DNA sequencing‐derived markers (1622 loci) identified 26 significant QTLs associated with the interspecific differences of body shape‐related traits. These QTLs had small to moderate effects, supporting polygenic inheritance of the body shape‐related traits. Each QTL was mostly located on different genomic regions, while colocalized QTLs were detected for some ecomorphologically relevant traits that are proxy of body and caudal peduncle depths, suggesting different degree of modularity among traits. The directions of the body shape QTLs were mostly consistent with the interspecific difference, and QTL sign test suggested a genetic signature of directional selection in the body shape divergence. Thus, we successfully elucidated the genomic architecture underlying the adaptive changes of the quantitative and complex morphological trait in a novel system.